2010
DOI: 10.3354/meps08521
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic resolution needed to describe invertebrate assemblages and to detect harvesting effects on coral reef ecosystems

Abstract: Due to the cost and time required for species identification, the taxonomic sufficiency approach has been developed in order to detect community response to a disturbance, using high taxonomic level without great loss of information. This concept has been widely applied to pollution monitoring studies but rarely to other forms of perturbations such as anthropogenic exploitation of marine resources. We applied this method both to soft-bottom (seagrasses) and hard-bottom (coralline) tropical invertebrate communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Considering the significant level, the sample size, and the need of taxonomist, this study suggested that familybased data analysis is the best option in analysing significant relationships between polychaete communities and macrophyte assemblages on rocky intertidal shores. This agrees with many previous studies that family is a good descriptor to analyse the community structure of invertebrates (Olsgard et al, 1997;Thompson et al, 2003;Jimenez et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Considering the significant level, the sample size, and the need of taxonomist, this study suggested that familybased data analysis is the best option in analysing significant relationships between polychaete communities and macrophyte assemblages on rocky intertidal shores. This agrees with many previous studies that family is a good descriptor to analyse the community structure of invertebrates (Olsgard et al, 1997;Thompson et al, 2003;Jimenez et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…These suggest that the polychaete samples do not have to be identified until species level to detect a significant change of polychaete communities. Hence, this supports previous studies that a higher taxonomic resolution can be used to do a rapid assessment on the environmental changes (Olsgard et al, 1997;Defeo and Lercari, 2004;Jimenez et al, 2010). In this study, it is true that order data are sufficient to analyse relationships between polychaetes and macrophytes, except to detect a significant change in order richness.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In contrast, species is better when obtaining information on areas with natu ral condition as it is more sensitive to natural processes (Warwick 1988a;Ferraro and Cole 1990). However, there was some variation in the pattern, particularly for hard bottom communities, wherein anthropogenic exploitation was only clearly evident at species level (Jimenez et al 2010). In coral reefs, both natural and anthropogenic disturbances occur, and it is clear that branching corals are most affected by any of the disturbances (Lewis 1998;Loya et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Olsgard et al (1998) found that variation in pattern between finer and coarser taxonomic resolution was greater in more pristine envi ronments. More recently, Jimenez et al (2010) showed that, for detecting changes due to anthropogenic exploi tation, the effective taxonomic resolution varied among habitats in tropical marine invertebrates. Some other studies have also indicated that the use of coarser reso lution may be enough to detect impact of environmental change and disturbance (Warwick 1988a(Warwick , 1988bSomer field and Clarke 1995).…”
Section: Monitoring Of Biological Systems Uses Different Taxonmentioning
confidence: 99%